Pengembangan Model Pembelajaran Meaningful Investigation Laboratory (MIL) untuk Meningkatkan Keterampilan Representasi Verbal, Grafik, dan Matematis (R-VGM) pada Pembelajaran Fisika SMA Di Jawa Timur - I Ketut Mahardika; Sri Astutik; Alfido Fauzy Zakaria; Aris Doyan; Susilawati Susilawati (Universitas Syiah Kuala, 2020)
The need for learning innovation is indispensable as a result of the development of the 21st century. In the 21st century learning there is a shift in student-centered learning from teacher-centered learning including physics learning. Physics learning requires innovation by not only doing learning activities in the classroom. Learning that is always done in class will make students become bored. Innovation of learning activities can be done in the laboratory as an appropriate alternative compared to conventional learning in the classroom. On the other hand in learning physics the skills that students must possess are skills in verbal, graphic and mathematical representations (R-VGM). Meaningful Investigation Laboratory (MIL) Learning Model is a 21st century learning innovation. The 21st century learning model has precondition, investigation, report, and reinforcement syntactic. In the first syntax, precondition, the R-VGM skill is developed from the opening question of physical phenomena. In the second syntax, namely investigation, R-VGM skills can be developed from scientific inquiry. In the third syntactic report, R-VGM skills can be developed from reporting the results of scientific investigations in and group discussions. In the fourth syntax, namely reinforcement, R-VGM skills can be developed from the matter of reinforcement. And in the fifth syntactic, reflection, R-VGM skills can be developed from the connection and reinforcement of the learning completed.